2022
DOI: 10.1111/jcal.12701
|View full text |Cite
|
Sign up to set email alerts
|

Examining effects of instructional strategies on student engagement in blended online courses

Abstract: Background: Blended online courses, which combine synchronous and asynchronous online activities, have expanded rapidly in higher education. How to enhance student engagement in such courses is unclear, although it is recognized that student engagement is malleable through instructional strategies.Objectives: Given the above, this study aims to examine the influence of categories of strategies on student engagement in blended online courses.Methods: A conceptual framework of instructional strategies indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Concerning technical skills, the journals show that we have been trying to apply the use of familiar instructional strategies in conjunction with knowledge of new instructional tools, such as using the 'Talk Time' function, on the digital platform to better manage the new blended learning experience for our students. This supports the findings of Heilporn et al (2022) who show that having effective instructional strategies within a blended learning environment creates clarity and better engagement for students. Although we did not interview students, we hope that as we continue to develop our competent use of the digital platform and seamlessly integrate the online and face-to-face elements of the course, we can help facilitate better student learning (Antonio, 2022).…”
Section: Which Teacher Competencies Are Perceived Assupporting
confidence: 87%
“…Concerning technical skills, the journals show that we have been trying to apply the use of familiar instructional strategies in conjunction with knowledge of new instructional tools, such as using the 'Talk Time' function, on the digital platform to better manage the new blended learning experience for our students. This supports the findings of Heilporn et al (2022) who show that having effective instructional strategies within a blended learning environment creates clarity and better engagement for students. Although we did not interview students, we hope that as we continue to develop our competent use of the digital platform and seamlessly integrate the online and face-to-face elements of the course, we can help facilitate better student learning (Antonio, 2022).…”
Section: Which Teacher Competencies Are Perceived Assupporting
confidence: 87%
“…Indeed, it was designed to draw a descriptive portrait of the strategies used by teachers in blended courses, as the first stage of a doctoral research. In a subsequent stage of the doctoral research, the effects of categories of teachers' strategies on student engagement dimensions were empirically investigated, according to the students' themselves (Heilporn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers’ cognitive support behaviors, such as providing direct instruction to diagnose misconceptions and organizing critical discourses to promote reflection, can facilitate cognitive engagement (Martono & Salam, 2017 ). Teachers’ emotionally supportive behaviors, such as fostering a positive learning environment and providing students with care and encouragement, can increase students’ emotional engagement (Heilporn et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have indicated that learning engagement is a key driver of online and blended learning and has a positive effect on academic persistence, completion and performance (Baranova et al, 2022;Phan et al, 2016). Fortunately, engagement is presumed to be malleable by direct intervention with contextual facilitators (Fredricks et al, 2019;Skinner & Pizter, 2012;Bond & Bedenlier, 2019;Heilporn et al, 2022).…”
Section: Introductionmentioning
confidence: 99%